Response to Hertz-Fowler and Berriman: Continuing tsetse and trypanosoma genome sequencing projects - Davila, A.M.R.; Majiwa, Phelix A.O.; Grisard, E.C.; Aksoy, S.; Hide, W. (Elsevier, 2004)
The recent genome initiatives of the neglected parasites Trypanosoma vivax and Trypanosoma congolense, and the vector tsetse are promising with regards to the data available in public databases. While these genome initiatives and the potential for developing new drugs and vaccines are admirable, it is notable that scientists from developing and endemic countries have had very little participation in the process of developing genome resources that are important in their fight against disease. The capacity exists within disease-endemic countries (DECs) to contribute to annotation and development of the analyses of the parasite and vector genomes. It is stated that both bioinformatics and research are becoming more necessary and essential in DECs. Therefore, there is an urgent need to undertake bioinformatics capacity-building in developing countries for several reasons, such as: (i) costs for bioinformatics research are lower; (ii) annotations would be performed in close collaboration with the sequencing centers in developed countries; (iii) the biology of the organism (pathogens and pests) is evident in DECs; hence, relevant genes can be evaluated as soon as they are identified, thus speeding up the evaluation and validation phase of candidate genes; (iv) validation of reagents or biotechnological products can often be performed in DECs on definitive host(s) affected by the pathogen, without undue restrictions inherent in conducting such validations where the disease is not endemic (e.g. developed countries); (v) a sense of joint ownership can be developed over the information derived from the sequence; and (vi) re-annotation is usually necessary and can be also be performed in developing countries. Additional justification includes the need to develop capacity to address local problems locally. The process of annotation, not just access to raw sequence reads from a website, requires the development of skills that can be subsequently applied with high impact in the local environment.